Tau hyperphosphorylation in the retinal ganglion cells is attenuated upon silencing of SHP2 phosphatase: Molecular and cell biology: Neurodegeneration versus neuroprotection. (7th December 2020) - Gupta, Vivek K.; Chitranshi, Nitin; Thananthirige, Kanshika Pushpitha Maha; Rajput, Rashi; Gupta, Veer Bala; Mirzaei, Mehdi; Basavarajappa, Devaraj; Graham, Stuart
Abstract: Background: Human and animal studies demonstrate that both amyloid precursor protein and phosphorylated Tau which are hallmark proteins associated with Alzheimer's disease (AD) pathology are perturbed in the retinal tissues. The accumulation of pTau in the retina in addition to the brain tissue suggests eye as a valuable structure for disease diagnosis and to study the disease mechanisms in neurodegenerative disease. Recent studies in human tissues and animal models have established a molecular overlap of AD with glaucoma in the eyes and both the diseases demonstrate altered amyloid beta and Tau phosphorylation profile. We show that Shp2 interacts with Tau protein in retina and silencing this phosphatase in the retinal ganglion cells using AAV2 mediated gene therapy can protect the retina. Method: Animal model of ocular hypertension was generated by repeat administration of polystyrene beads into the anterior chamber of rat eyes for 8 weeks resulting in sustained elevation of intraocular pressure (20.84±1.65 mmHg). Tau expression changes were investigated both in the animal model and human tissues obtained from the Sydney Eye bank (n=3) using immunohistochemical and WB. Silencing of Shp2 expression in the inner retina was achieved using intravitreal administration of AAV2 constructs under the control of CAG hybrid promoter. The animals were monitored for 2 months after Shp2 silencing and effects on Tau protein expression studied (n=48). Result: Increased Tau Ser404 phosphorylation was observed in both human glaucoma retinas (p<0.02; student t‐test) and in the animal model of glaucoma (p<0.05) in the WB and immunohistochemical analysis. Shp2 silencing (82±4%) was achieved using AAV2 administration and transduction was monitored using GFP staining. A 7.5±3‐fold downregulation Shp2 expression was achieved using shRNAmir that resulted in significant reduction of pTau Ser404 levels in the inner retina (p<0.028, Bornferroni post‐hoc test) indicating a regulatory effect of the phosphatase on the pTau levels. Conclusion: This study demonstrates that TauSer404 phosphorylation in the retina in vivo is regulated by Shp2 phosphatase. Targeted gene therapy approaches to modulate Shp2 expression can be used as a novel strategy to reduce Tau pathology in the neural tissues in various neurodegenerative disorders.